PHOTOCATALYTIC REMOVAL OF TR I- AND HEXA-VALENT CHROMIUM IONS FROM CHROME-ELECTROPL ATING WASTEWATER - Puangrat Kajitvichyanukul; Chulaluck Changul (Universitas Gadjah Mada, 2005)
A novel technique based on photocatalysis was applied to eliminate chromium ions, a toxic hazardous environmental pollutant. The photoreduction of each species of chromium (total, hexavalent, and trivalent chromiums) from chrome-electroplating wastewater was investigated using a titanium dioxide suspension under irradiation by a low-pressure mercury lamp. The initial concentration of total chromium was 300 mg/l. The applied conditions were the direct photocatalytic reduction process at pH 3.65 and the indirect photocatalytic reduction with added hole scavengers at the same solution pH. Results from both processes were comparatively discussed. Result show that chromium was not efficiently removed by direct photoreduction. In contrast, with the adding of hole scavengers, which were formate ions, the photoreduction of chromium was very favorable. Both hexavalent and trivalent chromiums were efficiently removed. The photocatalytic mechanism is purposed in this study.